2008
DOI: 10.1377/hlthaff.27.5.w360
|View full text |Cite
|
Sign up to set email alerts
|

Use Of Larger Versus Smaller Drug-Safety Databases Before Regulatory Approval: The Trade-Offs

Abstract: Although efforts to revamp the drug-safety system have been directed at strengthening postmarketing surveillance, strategies for the preapproval stage may be useful. One strategy would be to require larger sample sizes in preapproval safety databases. To evaluate the potential benefits and costs of this approach, we developed a hypothetical model to estimate the expected incremental number of adverse drug events that could be avoided in a postapproval population. We found that the potential to limit adverse ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 12 publications
(6 reference statements)
1
16
0
Order By: Relevance
“…This requires testing specific safety hypotheses with the appropriate sample size that reasonably balances the desire to limit the risk for potential post-approval adverse events with the need for efficient pathways for evaluating new therapies. 51 Ultimately, the degree of risk that must be “ruled out” in order to declare a treatment “safe” should be related to the degree and type of benefit (i.e., a drug that improves short-term symptoms only may be held to a higher standard of safety than one that improves mortality).…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…This requires testing specific safety hypotheses with the appropriate sample size that reasonably balances the desire to limit the risk for potential post-approval adverse events with the need for efficient pathways for evaluating new therapies. 51 Ultimately, the degree of risk that must be “ruled out” in order to declare a treatment “safe” should be related to the degree and type of benefit (i.e., a drug that improves short-term symptoms only may be held to a higher standard of safety than one that improves mortality).…”
Section: Safetymentioning
confidence: 99%
“…52 In order to be valid, a surrogate endpoint should meet clearly defined criteria: 1) the surrogate must be in the causal pathway from the intervention to the clinically relevant outcome, as reflected by a strong association between the surrogate and the target; and 2) there must be no important effects of the intervention on the outcome which are not mediated through or captured by the surrogate. 51 Because it is challenging to establish that these criteria are met, regulatory agencies have generally required that new therapies address clinically relevant outcomes before approval, and major policy decisions that favor one therapy over another should also be based on CER data that relates to clinically meaningful findings.…”
Section: Surrogatesmentioning
confidence: 99%
“…Evaluation of safety for new therapies should be guided by an understanding of the drug mechanism as well as by signals from earlier clinical study (e.g., renal dysfunction with nesiritide, ischemia with inotropic agents). This requires testing specific safety hypotheses with the appropriate sample size that reasonably balances the desire to limit the risk for potential post-approval adverse events with the need for efficient pathways for evaluating new therapies (51). Additionally, planning of phase III studies should include formal assessment of the upper boundary of risk (either relative or absolute) that can be excluded by the planned sample size.…”
Section: Safety End Pointsmentioning
confidence: 99%
“…Using discrete‐event simulation modeling of CV and gastrointestinal risks, these studies found that COX‐2 inhibitors increased RA population health (as measured by quality‐adjusted LYs) over a 1‐year horizon. When evaluating the consequences of additional safety testing on adverse events based on the rofecoxib withdrawal, expanded pre‐approval studies could have reduced adverse events, but an evaluation of both benefits and risks was beyond the study scope . Expanding pre‐approval studies can always increase the likelihood of detecting putative adverse effects of a drug, but a more comprehensive assessment of the benefits and risks specific to a particular situation is needed to determine what trial size provides the appropriate balance .…”
Section: Introductionmentioning
confidence: 99%